The Relationship of Early Providing MPASI and Recurrent Infectional Diseases with Stunting Incidents in Children Aged 1-5 Years in the Lawahing Public Health Care Working Area - Fitria Amin, Nurhayati; Meinar Sari, Gadis; Gita Ningrum, Astika (Jurnal sosial dan sains, 2024)
Background: Stunting which is a condition where there is failure to thrive in children under five years old (under five years) caused by chronic malnutrition so that the child is too short for his age. Providing complementary breast milk too early (less than 4 months) is an indirect factor causing stunting where early complementary breast milk food can cause various kinds of infectious diseases in children Purpose: to determine the relationship between giving early MPASI and recurrent infectious diseases to the incidence of stunting in children aged 1-5 years in the working area of the Lawahing Health Centre, Alor Regency, NTT Method: This research is an observational analytical study with a cross sectional approach. The sample from this study was 214 children aged 1-5 years who met the inclusion and exclusion criteria. Results: : research shows that there is a significant relationship between early complementary feeding and recurrent infectious diseases and the incidence of stunting in children aged 1-5 years (p value: <0.01). Conclusion: there is a significant relationship between early complementary feeding and recurrent infectious diseases with the incidence of stunting in children aged 1-5 years in the working area of the Lawahing Community Health Centre, Alor Regency, East Nusa Tenggara.